Silencing of MUC20 suppresses the malignant character of pancreatic ductal adenocarcinoma cells through inhibition of the HGF/MET pathway. Issue 46 (15th November 2018) - Chen, Syue-Ting; Kuo, Ting-Chun; Liao, Ying-Yu; Lin, Mei-Chun; Tien, Yu-Wen; Huang, Min-Chuan
Abstract Mucins are heavily glycosylated proteins that play critical roles in the pathogenesis of tumour malignancies. Pancreatic ductal adenocarcinoma (PDAC) is characterised by the aberrant expression of mucins. However, the role of mucin (MUC) 20 in PDAC remains unclear. PDAC is usually surrounded by a dense fibrotic stroma consisting of an extracellular matrix and pancreatic stellate cells (PSCs). The stroma creates a nutrient-deprived, hypoxic, and acidic microenvironment, and promotes the malignant behaviours of PDAC cells. In this study, immunohistochemical staining demonstrated that high MUC20 expression correlated with poor progression-free survival and high local recurrence rate of PDAC patients (n = 61). The expression of MUC20 was induced by serum deprivation, hypoxia, and acidic pH in PDAC cells. MUC20 knockdown with siRNA decreased cell viability, as well as migration and invasion induced by PSCs in HPAC and HPAF-II cells. In intraperitoneal, subcutaneous, and orthotopic injection models, MUC20 knockdown decreased tumour growth in immunodeficient mice. Phospho-RTK array and western blot analysis indicated that MUC20 knockdown decreased HGF-mediated phosphorylation of MET in PDAC cells. Moreover, HGF-induced malignant phenotypes could be suppressed by MUC20 knockdown. Co-immunoprecipitation revealed the physical association of MUC20 and MET. These findings suggest that MUC20 knockdown suppresses the malignant phenotypes of PDAC cells at least partially through the inhibition of the HGF/MET pathway and that MUC20 could act as a potential therapeutic target.